2021
DOI: 10.1093/braincomms/fcab246
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for the life-time risk prediction of Alzheimer’s disease: a systematic review

Abstract: Alzheimer’s disease is a neurodegenerative disorder and the most common form of dementia. Early diagnosis may assist interventions to delay onset and reduce the progression rate of the disease. We systematically reviewed the use of machine learning algorithms for predicting Alzheimer’s disease using single nucleotide polymorphisms and instances where these were combined with other types of data. We evaluated the ability of machine learning models to distinguish between controls and cases, while also assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…These scores have substantial potential utility in predicting lifetime risk of dementia. However, major challenges remain including how these scores can be used reliably at the individual level, their application across ethnicities, and whether their applicability varies at different stages of the lifecourse [ 15 ], plus the potential use of genetics and wide-ranging -omics generally in predictive modelling and machine learning [ 16 , 17 ].…”
Section: Geneticsmentioning
confidence: 99%
“…These scores have substantial potential utility in predicting lifetime risk of dementia. However, major challenges remain including how these scores can be used reliably at the individual level, their application across ethnicities, and whether their applicability varies at different stages of the lifecourse [ 15 ], plus the potential use of genetics and wide-ranging -omics generally in predictive modelling and machine learning [ 16 , 17 ].…”
Section: Geneticsmentioning
confidence: 99%
“…Sensory sensitivities associated with autism can also pose challenges for the dental team, impacting the provision of dental care. 1 As a result, autistic children and adolescents are more likely than their neurotypical peers to receive treatment under general anaesthesia. 1 Our team is collaborating with Stacey Venner, occupational therapist (OT) and experienced dental nurse who encountered first-hand the barriers to dental engagement for those from the autistic community and identified a need for multi-professional working that incorporates an occupational therapy perspective.…”
Section: A Partnership Between Occupational Therapy and Dentistrymentioning
confidence: 99%
“…1 As a result, autistic children and adolescents are more likely than their neurotypical peers to receive treatment under general anaesthesia. 1 Our team is collaborating with Stacey Venner, occupational therapist (OT) and experienced dental nurse who encountered first-hand the barriers to dental engagement for those from the autistic community and identified a need for multi-professional working that incorporates an occupational therapy perspective. Occupational therapy could be an ideal profession to assess and, where required, to provide a care plan for specific care needs of patients prior to dental visits.…”
Section: A Partnership Between Occupational Therapy and Dentistrymentioning
confidence: 99%
“…A review of illness prediction based on singlenucleotide polymorphisms has been undertaken by Ho et al [12]. A recent systematic review of ML algorithms in SNP data of Alzheimer's disease is shown by Rowe et al [13]. However, the main limitation of the research paper provided by Rowe et al [13] is the fact that they have utilized machine learning as a keyword for their search and presentation instead of investigating specific ML techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of ML algorithms in SNP data of Alzheimer's disease is shown by Rowe et al [13]. However, the main limitation of the research paper provided by Rowe et al [13] is the fact that they have utilized machine learning as a keyword for their search and presentation instead of investigating specific ML techniques. Hence, their review paper does not provide sufficient details on the contribution of various research in relation to the use of ML for the analysis of SNP data of AZ.…”
Section: Introductionmentioning
confidence: 99%